Media Literature Education To High School Students In Nimbokrang District, Jayapura Regency (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The advancement of digital media brings various impacts for the younger generation, especially students, both positive and negative impacts. From the positive impact on students, nowadays they are increasingly spoiled with various ease of accessing information, making friends, communicating, conducting online business activities, carrying out daily work activities. Meanwhile, from negative impacts such as: lack of physical activity, reducing student learning, being easily provoked through hoax news, inefficient in costs, reducing study time and others. Community service activities, through digital media literacy education for students, aim to: increase digital literacy skills for students who are classified as vulnerable to information exposure. The methods used are: socialization and discussion, training, practice of using digital media. With the stages of activities: preparation, implementation and evaluation. Digital media literacy education activities result in an increase in students' knowledge and skills after following the series of materials provided. It is recommended that the school should be more active in conducting supervision, training and mentoring for students in the use of digital media to support studentachievement in school.